Improvement of nutritional value of instant noodles By fortifying with catfish (pangasius hypophthalmus) flour - Depri Gusriadi; Mery Sukmiwati; Dahlia ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate the nutritional value of instant noodlesfortified with catfish flour. Instant noodles were prepared from a mixture of wheatflour (50%), sweat potato flour (10%), egg (15%), salt (0,7%), water (23%),cooking oil (0,3%) and Carboxy Methyl Cellulose (1%). The noodles wereprepared by fortifying the mixture with catfish flour at a level of 0%, 5%, 10%,and 15 % respectively. Instant noodles was evaluated for sensory quality andproximate composition (moisture, protein, carbohydrate, and fat). The resultshowed that instant noodles fortified with 15% of catfish flour has the bestsensory and proximate quality. Moisture, protein, carbohydrate, and fat for theinstant noodles was 3,88%, 36,67%, 21,00%, and 9,03% respectively.Keyword : Catfish flour, instant noodles, Pangasius hypophthalmus